An Endocrinological approach to Cornelia de Lange Syndrome - Mirela Elena Iancu; Alice Ioana Albu; Raluca Maria Vlad; Dragos Nicolae Albu (Amaltea Medical Publishing House, 2022)
Cornelia de Lange syndrome is a developmental disorder with a great degree of clinical and genetical variability characterized by typical facial features, growth impairment and multi-organ anomalies. It is caused by mutations in the cohesin complex that is involved in regulation of gene expression. Growth disturbances are a major feature of the syndrome and have various underlying mechanisms. Other associations regarding endocrine function are represented by disturbances in the hypothalamic-pituitary axis, decreased bone density associated with fractures and genital malformations associated with menstrual irregularities and altered fertility.